2017
DOI: 10.1063/1.4986174
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio velocity-field curves in monoclinic β-Ga2O3

Abstract: We investigate the high-field transport in monoclinic β-Ga2O3 using a combination of ab initio calculations and full band Monte Carlo (FBMC) simulation. Scattering rate calculation and the final state selection in the FBMC simulation use complete wave-vector (both electron and phonon) and crystal direction dependent electron phonon interaction (EPI) elements. We propose and implement a semi-coarse version of the Wannier-Fourier interpolation method [F. Giustino, M. L. Cohen, and S. G. Louie, Physical Review B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…Anyway, the observed agreement supports the validity of the RTA approach proposed in this work, and enables its extension to other semiconductors with nearly isotropic effective mass and multiple PO vibrational modes. The validity of the first principle calculations of [35][36][37] is also indirectly confirmed.…”
Section: J Wmentioning
confidence: 63%
See 1 more Smart Citation
“…Anyway, the observed agreement supports the validity of the RTA approach proposed in this work, and enables its extension to other semiconductors with nearly isotropic effective mass and multiple PO vibrational modes. The validity of the first principle calculations of [35][36][37] is also indirectly confirmed.…”
Section: J Wmentioning
confidence: 63%
“…It is to be said that Chang and James's approach can be applied to β-Ga 2 O 3 , thanks to the nearly spherical CB (nearly isotropic electron effective masses) and negligible mobility anisotropy as mentioned in the introduction. Dispersion relations of all the vibrational modes of β-Ga 2 O 3 were derived from first principles, and the anisotropic scattering probabilities W k j ( ) for each IR active mode j were calculated at T=300 K [35][36][37] and then spherically averaged over the Brillouin zone. After averaging, however, the information on the anisotropy of the LO-TO split is lost.…”
Section: Polar Optical Phonon Momentum Scattering Timementioning
confidence: 99%
“…For the ideal HFCV calculation of SiO 2 /b-Ga 2 O 3 MOSCAP, the relative permittivity of Ga 2 O 3 is assumed to be 10 and its electron effective mass ratio is 0.28 which is isotropic near the conduction band minima. 1,[25][26][27] This calculation gives a D it vs. DE curve. 28 However, the valid range of energies (DE) for quantitative D it extraction is reduced, which is limited by the temperature, the high frequency, and the low frequency (QSCV) 20 of the measurement.…”
mentioning
confidence: 99%
“…There have been a few low-field transport calculation reports [20,21] in this material revealing that the long-range polar optical phonon (POP) electron-phonon interactions (EPI) limit the electron mobility. Recently, the authors reported a high-field transport calculation including full-band EPI to predict velocity-field curves in this material [22] for an electric field up to 0.4 MV/cm. However, as the electric field is further increased, interband transitions and electron ionization become important.…”
Section: Introductionmentioning
confidence: 99%